Blood pressure telemonitoring and remote counseling of hypertensive patients: pros and cons - M. V. Ionov; N. E. Zvartau; A. O. Konradi; E. V. Shlyakhto (Российский кардиологический журнал, 2020)
Home blood pressure monitoring (HBPM) is strongly recommended by current guidelines as an effective out-of-office diagnostic and monitoring tool in patients with hypertension (HTN). However, there are personal, cultural, logistic difficulties owing to low effectiveness of HBPM. These put HBPM at a disadvantage in routine clinical practice. As such, telehealth solutions are of special interest nowadays, particularly blood pressure telemonitoring (BPTM) with or without remote counseling. BPTM might become something of digital assistant in the long-term patients’ follow-up and it fits well into the practice of continuity of medical care. The purpose of this review is to highlight not only the benefits of BPTM, but important discrepancies that may impede its widespread implementation in everyday clinical work. Critical comments address the lack of long-term, high-quality studies, absence of hard clinical outcomes and uncertainty on the best technical performance.